2004
DOI: 10.1111/j.1365-2265.2004.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Marked and sustained increase in bone mineral density after parathyroidectomy in patients with primary hyperparathyroidism; a six‐year longitudinal study with or without parathyroidectomy in a Japanese population

Abstract: We demonstrated that PTX led to marked and sustained increases in BMD not only at L2-L4 but also at R1/3 in Japanese pHPT patients, including postmenopausal women. The preoperative PTH level could be a clinically useful index for predicting long-term BMD changes after PTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
5
34
2
3
Order By: Relevance
“…Observational studies have also demonstrated significant improvement in BMD after PTx (114,135,138,139). In a prospective cohort of 121 patients with PHPT followed for 10 years, there was an increase of 12% to 15% in BMD of patients undergoing PTx (135), especially in the lumbar spine and hip (B-2B).…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies have also demonstrated significant improvement in BMD after PTx (114,135,138,139). In a prospective cohort of 121 patients with PHPT followed for 10 years, there was an increase of 12% to 15% in BMD of patients undergoing PTx (135), especially in the lumbar spine and hip (B-2B).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Most of the bone loss occurred after the first 8 years of follow-up. Most studies (135,(138)(139)(140)(141)(142)(143), but not all (143,144) do not show reduction in BMD at any sites during the first years of observation without intervention (B-2B).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Other studies have also shown this positive effect of PTx on BMD, supporting the notion that osteopenia and osteoporosis are at least partially reversible after PTx (15)(16)(17). In our study, the limited number of X-rays performed in the study population combined with the small number of fractures sustained before or after PTx precludes a meaningful analysis of an effect of PTx on fracture risk.…”
Section: Discussionmentioning
confidence: 42%
“…In PHPT, the importance of achieving cure has been highlighted in a number of studies focusing on the effect of PTx on bone mineral density (BMD), nephrolithiasis, and neurocognitive function (14)(15)(16). Patients who are cured show a significant post-operative increase in bone mass, with BMD remaining significantly above baseline for up to 15 years of follow-up (17).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term follow up of these patients indicates a 10 to 12 percent improvement in bone density at the lumbar spine and femoral neck over 10 years (31,37). In patients who have nephrolithiasis, surgery is of clear benefit in reducing the incidence of recurrent stones (38). Vague or constitutional symptoms may or may not improve after surgery, while hypertension and peptic ulcer disease, if present, are unlikely to remit.…”
Section: Results Of Surgerymentioning
confidence: 99%